The Effect of Practice Arrangement (Contextual Interference) on Acquisition, Retention and Transfer of Coincidence Anticipation Tasks with Constant, Increasing and Decreasing Speeds - Mohammad ali Aslankhani; Alireza Farsi; Hojjat Zamani; Zahra Fathi (University of Tehran, 2010)
The present study aimed to examine the effect of contextual interference on acquisition, retention and transfer of coincidence anticipation task with constant, increasing and decreasing speeds. 36 male physical education participants from Shahid Beheshti University were voluntarily selected and randomly divided into three groups (12 subjects each group) and performed coincidence timing tasks with Bassin anticipation timing. In this research, three separate experiments were used. Experiments consisted of constant speed, increasing speed and decreasing speed. Subjects participated in pretest, acquisition, blocked retention, random retention and transfer tests. Absolute temporal errors were analyzed by one-way ANOVA, ANOVA with repeated measures and Bonferroni post hoc tests (P